2022
DOI: 10.3390/jcm11216528
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Kidney Diseases That Require a Differential Diagnosis from Autosomal Dominant Polycystic Kidney Disease (ADPKD)

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary cystic kidney disease, with patients often having a positive family history that is characterized by a similar phenotype. However, in atypical cases, particularly those in which family history is unclear, a differential diagnosis between ADPKD and other cystic kidney diseases is important. When diagnosing ADPKD, cystic kidney diseases that can easily be excluded using clinical information include: multiple simple renal cysts, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…Henske et al have demonstrated that loss-of-function mutations in the TSC1 or TSC2 genes can interfere with the structure and function of the cilia in renal tubular cells, thereby contributing to the formation of cysts in the kidneys [11]. Multicystic dysplastic kidney (MCDK) disorder was traditionally assumed to be a developmental anomaly in which the renal parenchyma fails to develop, leading to the presence of primitive ducts, cysts, and, potentially, tissues of extrarenal origin [12,13]. However, the research conducted by Harris et al suggests that MCDK, in its severe form, can be classified as part of the broader spectrum of ciliopathies, requiring further research to comprehend its underlying molecular mechanisms [14].…”
Section: Cystic Kidney Disease As Part Of the Ciliopathies Spectrummentioning
confidence: 99%
“…Henske et al have demonstrated that loss-of-function mutations in the TSC1 or TSC2 genes can interfere with the structure and function of the cilia in renal tubular cells, thereby contributing to the formation of cysts in the kidneys [11]. Multicystic dysplastic kidney (MCDK) disorder was traditionally assumed to be a developmental anomaly in which the renal parenchyma fails to develop, leading to the presence of primitive ducts, cysts, and, potentially, tissues of extrarenal origin [12,13]. However, the research conducted by Harris et al suggests that MCDK, in its severe form, can be classified as part of the broader spectrum of ciliopathies, requiring further research to comprehend its underlying molecular mechanisms [14].…”
Section: Cystic Kidney Disease As Part Of the Ciliopathies Spectrummentioning
confidence: 99%
“…Recently, research on hereditary renal cystic diseases such as polycystic kidney disease (PKD) and nephronophthisis (NPHP) has exponentially progressed, facilitating the ongoing identification of genetic variants that lead to the development of adult PKD with the use of laboratory animals [ 1 ]. This review focuses on the utility of laboratory rodent models in the development of treatment strategies for renal cystic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The NPHP1 ‐related disorders are autosomal recessive syndromes caused by pathogenic variants, commonly homozygous deletions, in the NPHP1 gene on chromosome 2q13 and are all associated with nephronophthisis (NPHP), a prevalent hereditary kidney disease that ultimately progresses to end‐stage renal disease. NPHP is typically characterized by corticomedullary cysts, polyuria, polydipsia, hyponatremia, and other signs of progression to impaired kidney function 1 . Mutation of NPHP1 is the most common cause of NPHP 2 .…”
Section: Introductionmentioning
confidence: 99%
“…NPHP is typically characterized by corticomedullary cysts, polyuria, polydipsia, hyponatremia, and other signs of progression to impaired kidney function. 1 Mutation of NPHP1 is the most common cause of NPHP. 2 Juvenile nephronophthisis‐1 is characterized by NPHP that progresses to end stage renal disease at a mean age of 13 years.…”
Section: Introductionmentioning
confidence: 99%